2019
DOI: 10.1016/j.palaeo.2019.109362
|View full text |Cite
|
Sign up to set email alerts
|

Time-richness and phosphatic microsteinkern accumulation in the Cincinnatian (Katian) Ordovician, USA: An example of polycyclic phosphogenic condensation

Abstract:  Phosphatic microsteinkern-rich sediments are time-rich shell beds  Carbonate textural maturity may result from minor stratigraphic condensation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Principally, this may mean that the authors of the following source found the precedent hypothesis reasonable to a certain degree. For instance, Lam et al [40] noted tsunamis interpreted previously in the Late Ordovician sedimentary successions of the Cincinnati Basin. It is also reasonable to note the work by Meinhold et al [50], who discussed the earlier proposal by Parnell [51] of the possible impact-triggered, global-scale episode of mass wasting in the Middle Ordovician.…”
Section: Summary Of the Evidence Collected From The Literaturementioning
confidence: 98%
“…Principally, this may mean that the authors of the following source found the precedent hypothesis reasonable to a certain degree. For instance, Lam et al [40] noted tsunamis interpreted previously in the Late Ordovician sedimentary successions of the Cincinnati Basin. It is also reasonable to note the work by Meinhold et al [50], who discussed the earlier proposal by Parnell [51] of the possible impact-triggered, global-scale episode of mass wasting in the Middle Ordovician.…”
Section: Summary Of the Evidence Collected From The Literaturementioning
confidence: 98%
“…Clarifying the link between paleoenvironment and fossilization is important to understand what closed the taphonomic window that fostered these styles of preservation in the later early and middle Cambrian globally (Porter 2004) (see Figure 3). The occurrence of phosphatized and/or glauconitized fossils at other intervals in the Paleozoic (Dattilo et al 2019, Dzik 1994 and Mesozoic (Maxwell et al 2021, Pruss et al 2018 suggests that recurring environmental factors led to these styles of preservation. In this case, the small size of skeletal material (and organismal volume) coupled with early oscillating porewater redox conditions must be critical factors in these modes of preservation and to marine authigenesis of the Cambrian more broadly.…”
Section: Small Shelly Fossil Preservation In the Cambrianmentioning
confidence: 99%
“…Datilo et al . 2019). This particular style of fossilization is best known from Cambrian deposits, where small shelly fossils record remnants of some early biomineralizers of the Cambrian Explosion and occur across clades.…”
Section: Geological Settingmentioning
confidence: 99%
“…Whilst scattered occurrences of small shelly‐style fossilization have been reported from other time periods (Dzik 1994; Datillo et al . 2019; Freeman et al . 2019), the best known and most intensively studied occurrences are Cambrian small shelly fossils (SSFs), in part because the diversity of organisms preserved in this way is not well represented in macrofossil assemblages.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation